2010
DOI: 10.1016/j.jacc.2009.07.069
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Cardiovascular Risk Assessment in Elderly People

Abstract: Objectives Determine if serial measurement of N-terminal pro B-type natriuretic peptide (NT-proBNP) in community dwelling elderly would provide additional prognostic information to traditional risk factors. Background Accurate cardiovascular risk stratification is challenging in the elderly. Methods NT-proBNP was measured at baseline and 2-3 years later in 2,975 community-dwelling older adults free of heart failure in the longitudinal Cardiovascular Health Study. This investigation examined the risk of new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
89
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 34 publications
5
89
0
Order By: Relevance
“…The addition of sST2 to demographics and clinical risk factors only modestly improved discrimination and risk reclassification for incident HF and cardiovascular death. However, similar to other cohorts, increasing levels of ST2 in older adults in a cross‐sectional analysis were associated with higher risk demographics, increased comorbidities, and increasing levels of cardiac specific and noncardiac specific biomarkers that have been independently associated with poorer outcomes 18, 27, 28, 39…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The addition of sST2 to demographics and clinical risk factors only modestly improved discrimination and risk reclassification for incident HF and cardiovascular death. However, similar to other cohorts, increasing levels of ST2 in older adults in a cross‐sectional analysis were associated with higher risk demographics, increased comorbidities, and increasing levels of cardiac specific and noncardiac specific biomarkers that have been independently associated with poorer outcomes 18, 27, 28, 39…”
Section: Discussionsupporting
confidence: 74%
“…Participants (N=5201) initially enrolled in 1989–1990, and an black supplemental cohort (N=687) enrolled in 1992–1993. This ancillary analysis included participants without a previous diagnosis of HF in whom measures of amino terminal pro‐B‐type natriuretic peptide (NT‐proBNP) and high‐sensitivity cardiac troponin T (hs‐cTnT) had already been performed as previously described27, 28 and with available stored serum for measurement of sST2. Figure 1 is a flow diagram of CHS participants who met criteria or were excluded for the present sST2 analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DeFilippi et al [11 ]found that increased levels of NT-proBNP over time predicted a higher risk of new-onset HF and CV-related death, independent of traditional risk factors and abnormalities on ECG and echocardiography. Our findings in patients with stable CAD are similar to those of deFilippi et al [11] in that the prognostic value of NT-proBNP appeared to follow a threshold effect, whereby the greatest change in NT-proBNP had the most robust association with adverse clinical outcomes. We observed this threshold at a 5-year change in NT-proBNP levels of ≥223 pg/mL, which was similar to the threshold of ≥190 pg/mL found in the study by deFilippi et al [11].…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of community-dwelling adults, increases in NT-proBNP levels over the long-term were associated with adverse CV outcomes [10,11]. Currently, however, it is not known whether long-term changes in levels of NT-proBNP predict subsequent adverse CV outcomes among patients with stable CAD.…”
Section: Introductionmentioning
confidence: 99%